2012
DOI: 10.1039/c2em30254c
|View full text |Cite
|
Sign up to set email alerts
|

An economic appraisal of using source separation of human urine to contain and treat endocrine disrupters in the USA

Abstract: Elevated concentrations of estrogens in natural waters pose a significant threat to public health and aquatic ecosystems. Both natural (estrone, 17β-estradiol and estriol) and synthetic (17α ethynylestradiol) estrogens, ubiquitous in wastewater effluents and receiving waters, have been shown to affect the endocrine system of human and aquatic life. The effects vary from cancer to sex reversals at levels as low as parts per trillion in sensitive organisms. Separation of urine, which constitutes only about 1% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Furthermore, struvite precipitation of source separated urine reduces nutrient emissions, offsets commercial fertilizer production, and reduces cadmium emissions due to commercial fertilizers. These results are similar to other LCA studies that found that potable water savings, electricity savings, reduction in nutrient loading, and reduced cadmium emissions from commercial fertilizers in the environment are major benefits gained from urine source separation (Berndtsson, 2006, Ishii and Boyer, 2015, Lam et al, 2015, Lamichhane and Babcock, 2012, Ronteltap et al, 2007. Results of the Monte Carlo simulation indicate that uncertainty does not affect the overall trends for the total environmental impact, where AWWT and BWWT,O3 have greater observed environmental impact compared with the urine source separation and the vacuum sewer scenarios had the largest impact among the source separation scenarios.…”
Section: Overall Comparison Of Scenariossupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, struvite precipitation of source separated urine reduces nutrient emissions, offsets commercial fertilizer production, and reduces cadmium emissions due to commercial fertilizers. These results are similar to other LCA studies that found that potable water savings, electricity savings, reduction in nutrient loading, and reduced cadmium emissions from commercial fertilizers in the environment are major benefits gained from urine source separation (Berndtsson, 2006, Ishii and Boyer, 2015, Lam et al, 2015, Lamichhane and Babcock, 2012, Ronteltap et al, 2007. Results of the Monte Carlo simulation indicate that uncertainty does not affect the overall trends for the total environmental impact, where AWWT and BWWT,O3 have greater observed environmental impact compared with the urine source separation and the vacuum sewer scenarios had the largest impact among the source separation scenarios.…”
Section: Overall Comparison Of Scenariossupporting
confidence: 89%
“…Human urine is the primary contributor of pharmaceuticals in municipal wastewater but only constitutes 1% of the total volumetric flow (Joss et al, 2005, Larsen andGujer, 1996). Urine source separation has been proposed as a more efficient method to remove and/or destroy pharmaceuticals as opposed to centralized biological wastewater treatment because pharmaceuticals are present at much higher concentrations in undiluted urine (Lamichhane and Babcock, 2012). In addition, human urine contributes 80% of the nitrogen (N) and 50% of the phosphorus (P), indicating separate 32 treatment of urine may have significant impacts on centralized wastewater treatment (Larsen and 33 Gujer, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 70% of ingested pharmaceuticals intended for human use are excreted in urine as either the parent compound or its metabolites (Lienert et al, 2007a). For this reason, urine sourceseparation and treatment is a proposed method to reduce pharmaceutical loading to the environment by diverting undiluted urine from domestic wastewater (Lamichhane and Babcock, 2012). Urine source-separation and treatment is also of interest as an alternative approach to address excess nitrogen and phosphorus loading to aquatic systems (Larsen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, w70% of consumed pharmaceuticals were excreted in human urine as the active ingredient and metabolites (Lienert et al, 2007b). Accordingly, source separation of human urine has been proposed to decrease the load of pharmaceuticals to wastewater plants and the environment (Lamichhane and Babcock, 2012) as well as produce urine-derived fertilizer (Kirchmann and Pettersson, 1995). The basis for urine source separation is that the excreted pharmaceuticals are present at much higher concentrations in undiluted urine than domestic wastewater (Winker et al, 2008a) and thus can be treated more efficiently.…”
Section: Introductionmentioning
confidence: 99%